Bulliform Cell‐Induced Leaf Curling Contributes to Water Loss and Water Potential Regulation of Bamboos During Dry Season - Aritsara, Amy Ny Aina; Cao, Kun‐Fang; Zhang, Yong‐Jiang; Han, Lu; Maenpuen, Phisamai; Zhang, Shu‐Bin; Zhao, Gao‐Juan; Wei, Yang; Liu, Jia‐Bao; Yu, Jia‐Rui; Chen, Ya‐Jun (Physiologia plantarum, 2025)
ABSTRACT A balanced water supply and demand is critical for plant growth and survival. Despite the ecological importance of bamboos in tropical ecosystems, the water regulation mechanisms across bamboo species remain poorly understood. This study quantified the relative contributions of soil water‐uptake depth, leaf water storage and retention capacity, and related anatomical traits to daytime and seasonal variations in leaf water potential across nine co‐occurring bamboo species. The results revealed that the studied bamboos obtained 50% of their water from soil depth shallower than 32 cm. The studied bamboo species have low saturated water content (SWC) and short‐to‐average leaf dehydration time to 70% of its SWC (T70 = 74.5–250.4 min). They exhibited large interspecific variation in dry‐season midday leaf water potential (Ψdry.md). Higher T70 (i.e., slow desiccation rate) was significantly correlated with less negative Ψdry.md, but Ψdry.md was not related to soil water‐uptake depth or leaf water storage. Leaf anatomy, curling rate, and curling intensity analyses demonstrated two complementary water regulation mechanisms: (1) high density of bulliform cells enabled rapid leaf curling under water deficit, resulting in high predawn water potential in the dry season; and (2) large bulliform cell aperture promoted intensive leaf area reduction during water stress, slowing water loss, thus enabling less negative Ψdry.md. This study provides evidence of the synergy between bulliform cell structures and leaf water retention capacity across bamboo species and their contribution to water regulation under drought stress, highlighting structural adaptations in the leaves of bamboos enabling their success in seasonal tropical forests.